Prevalence and correlates of cardiometabolic multimorbidity among hypertensive individuals: a cross-sectional study in rural South Asia—Bangladesh, Pakistan and Sri Lanka. Issue 9 (4th September 2019) - Feng, Liang; Jehan, Imtiaz; de Silva, H Asita; Naheed, Aliya; Farazdaq, Hamida; Hirani, Samina; Kasturiratne, Anuradhani; Ranasinha, Channa D; Islam, Md Tauhidul; Siddiquee, Ali Tanweer; Jafar, Tazeen H
Abstract : Objective: To determinate the prevalence and correlates of cardiometabolic multimorbidity (CMM), and their cross-country variation among individuals with hypertension residing in rural communities in South Asia. Design: A cross-sectional study. Setting: Rural communities in Bangladesh, Pakistan and Sri Lanka. Participants: A total of 2288 individuals with hypertension aged ≥40 years from the ongoing Control of Blood Pressure and Risk Attenuation- Bangladesh, Pakistan and Sri Lanka clinical trial. Main outcome measures: CMM was defined as the presence of ≥2 of the conditions: diabetes, chronic kidney disease, heart disease and stroke. Logistic regression was done to evaluate the correlates of CMM. Results: About 25.4% (95% CI 23.6% to 27.2%) of the hypertensive individuals had CMM. Factors positively associated with CMM included residing in Bangladesh (OR 3.42, 95% CI 2.52 to 4.65) or Sri Lankan (3.73, 95% CI 2.48 to 5.61) versus in Pakistan, advancing age (2.33, 95% CI 1.59 to 3.40 for 70 years and over vs 40–49 years), higher waist circumference (2.15, 95% CI 1.42 to 3.25) for Q2–Q3 and 2.14, 95% CI 1.50 to 3.06 for Q3 and above), statin use (2.43, 95% CI 1.84 to 3.22), and higher levels of triglyceride (1.01, 95% CI 1.01 to 1.02 per 5 mg/dL increase). A lower odds of CMM was associated with being physically active (0.75, 95% CI 0.57 to 0.97). A weak inverted J-shaped association between International Wealth Index and CMM was found (p for non-linear=0.058), suggesting higher risk in the middle than higher or lower socioeconomic strata. Conclusions: CMM is highly prevalent in rural South Asians affecting one in four individuals with hypertension. There is an urgent need for strategies to concomitantly manage hypertension, cardiometabolic comorbid conditions and associated determinants in South Asia.